1914. Society and parliament: reflections on a crisis - Luna, Pablo F. (1989)
​The context of a medium-importance financial crisis-such as the 1914 one, at the beginning of the Great War, that would present a series of problems new to Peru, has given us the opportunity to probe into the practices and idiosyncrasies of the political members of the Peruvian State of that time. By analyzing the Journal of Parliamentary Debates -a source for historical research still little used- we have been able to conretely examine the process of adoption of economic and financial policies, and the conflicts inherent to it, in the context of the beginning of the first world war. By observing the relationships between the Political Power and the Civil Society we have been able to verify some constants about the way policy decisions are taken. That is, we have been able to analyze, in terms of a recent past, some of the evolucions of the contemporary peruvian political system, which today appear to us a syntetical and condensed, or even petrified.